Physical activity in atopic dermatitis: a narrative review - Leszyńska, Agnieszka; Bałoniak, Julia; Bałoniak, Zuzanna; Jonkisz, Aleksandra; Doligalska, Michalina; Stremel, Aleksandra; Bachoń, Emilia; Skurzyńska, Gabriela; Kozłowska, Dominika (Quality in Sport, 2024)
Atopic dermatitis (AD) is a common chronic skin disease that impacts various aspects of a patient’s life. Among numerous triggers, there is a specific group of factors that may arise during physical activity. Due to skin-related issues, which can be both a significant obstacle and a source of fear regarding symptom exacerbation, the habits and behaviors of patients with AD differ from those of the general population. Understanding these changes can provide valuable insights into which types of sports or physical activities should be recommended by physicians, physiotherapists, or other professionals involved in sports and health. In this review, we analyze studies conducted on this topic and aim to draw conclusions on how to best promote physical activity in patients with AD while minimizing its negative impact on their skin. We emphasize the lack of essential studies that involve engaging patients with AD in various forms of physical activity and subsequently assessing their skin condition and symptom severity after exercise.